RNA-seq analysis to unravel the molecular players involved in implantation/ rejection of human tumor cells in zebrafish - Domingues, Micaela Oliveira (2021)
Tese de mestrado em Bioinformática e Biologia Computacional, Faculdade de Ciências, Universidade de Lisboa, 2020